Ex ante and ex post effects of hybrid index insurance in Bangladesh - Hill, Ruth Vargas; Kumar, Neha; Magnan, Nicholas; Makhija, Simrin; de Nicola, Francesca; Spielman, David J.; Ward, Patrick S. (Elsevier, 2019)
This study assesses both the demand for and effectiveness of an index insurance product designed to help smallholder farmers in Bangladesh manage crop production risk during the monsoon season. Villages were randomized into either an insurance treatment or a comparison group, and discounts and rebates were randomly allocated across treatment villages to encourage insurance take-up and to allow for the estimation of the price-elasticity of insurance demand. Among those offered insurance, we find demand to be fairly price elastic, with discounts significantly more successful in stimulating demand than rebates. Purchasing insurance yields both ex ante risk management effects as well as ex post income effects on agricultural production practices. The risk management effects lead to an expansion of cultivated area with concomitant increases in agricultural input expenditures during the monsoon season. The income effects lead to more intensive rice production during the subsequent dry season, with more intensive use of both irrigation and fertilizers, resulting in higher yields and higher total rice production.